Leisure education program planning - Dattilo, John (Champaign, IL Sagamore Venture, 2021)
The intention of the book is to share information with readers to develop a sense of competence in providing a balanced and systematic approach to leisure education that helps people experience wonder and amazement through leisure. To achieve this purpose, the book provides a sequential explanation about how to transform the model (depicted on the book cover) into a guide for planning, implementing, and evaluating leisure education. As you read these three paragraphs, see if you can find the words bolded or italicized in this preface on the book cover as words or objects! The book describes synergistic goals of leisure education to assist people in experiencing leisure, embracing happiness, and flourishing. The approach described in this text offers guidance for readers to become effective professionals. This text describes principles on which to base service delivery and then application of those principles to situations we encounter. Principles identified in this book are intrinsic motivation, self-determination, flow, optimal arousal, savoring, and positivity. As we learn more about ways our communities and countries function, relevance of social justice becomes clearer; therefore, the book describes leisure education and ways it connects to social justice. The book also identifies components of leisure education, highlighting the value of developing an ethic, acquiring knowledge, gaining skills, managing challenges, becoming self-aware, and exploring opportunities. Aspects of developing programs include addressing content areas and identifying cultural and ability considerations as well as process considerations representing a systems approach using teaching techniques and processing strategies. The model presented on the cover creates balance and is systematic, both globally relevant. To reflect international perspectives, the model contains both Western and Eastern symbols. For example, since the Chinese philosophy of Yin and Yang emphasizes the value of balancing sometimes opposing yet complementary forces to achieve precious experiences, the yin yang symbol is at the center of the model. Similarly, given a scale is a symbol in Western cultures reflecting balance; such a scale acts as the support structure for the model. The base of the scale identifies five examples of ways to achieve a balanced approach to life and leisure including pursuits, leisure, experiences, blessings, and reciprocity. To indicate a systematic approach to leisure education, the model contains arrows designating linear directionality and progression in conjunction with circles denoting circular integrity and integration. Many Eastern cultures associate circles with interconnections of much that is in the world and the concept of community harmony. Historically, some Native American Indian tribes and Western mapmakers used arrows to represent movement and directionality. The notion of linearity, often identified by a straight line or arrow, frequently connects to Western thinking about desired states of independence and self-fulfillment. Throughout the model, arrows and circles illustrate the cyclical nature of leisure education and that learning involves collaboration between learners, instructors, and communities. The final section of the book contains examples of specific field-tested and researched programs to help readers improve understanding of service delivery. As we grow through leisure education, we tend to manage challenges to leisure and gravitate to positive experiences. These positive encounters transport us toward achieving the ultimate goals of experiencing leisure, being happy, and flourishing. In conclusion, I hope you find this fifth edition of the book to be meaningful and helpful in facilitating leisure through leisure education
1. An introduction: a journey -- 2. Goals of leisure education, part I: leisure -- 3. Goals of leisure education, part II: happiness and flourishing -- 4. Principles of leisure education -- 5. Leisure education -- 6. Constraints to leisure -- 7. A balanced approach to leisure education -- 8. Recommendations for leisure education -- 9. Effects of leisure education -- 10. Components of leisure education -- 11. Cultural considerations for leisure education -- 12. Ability considerations -- 13. Systematic programming for leisure education -- 14. Teaching techniques for leisure education -- 15. Processing in leisure education
Keywords: Leisure -- study and teaching; Recreation leadership